Sequential Information Flow and Real-Time Diagnosis of Swiss Inflation: Intra-Monthly DCF Estimates for a Low-Inflation Environment - Andreas Fischer; Marlene Amstad (Swiss National Bank, Study Center Gerzensee, 2004)
The timely release of macroeconomic data imposes a distinct structure on the panel: the clustering and sequential ordering of real and nominal variables. We call this orderly release of economic data sequential information flow. The ordered panel generates a new class of restrictions that are helpful in interpreting the real-time estimates of monthly core inflation through the identification of turning points and structural shocks. After establishing the sought-after properties (of smoothness, stability, and forecasting) for core inflation, we turn to the discussion of real-time diagnosis for a low inflation environment. This is done in the context of weekly estimates of Swiss inflation. The intra-monthly estimates for core inflation find that it is worthwhile to update this measure at least twice a month.
Keywords: E52; E58; 330; Inflation; Common Factors; Sequential Information Flow; Inflation; Messung; Schätzung; Schweiz